Uso e ocupação do solo e escoamento superficial na Bacia Hidrográfica do Rio Cascavel - Arndt, Marcos Alexandre (2009)
The Brazilian municipality presented significant urbanization process, what caused the expansion of urban areas, and consequently increased the impermeable areas. The measure that the city is urbanized increases the peak discharge resultants of the water runoff, what can provoke problems as floods of closeness areas to the drainage channels. Know the influence of the water runoff in watershed is primordial for its management, and estimations or the sceneries of future occupations helps to support the address planning adapted for the Brazilian watershed. Starting from this problematic situation this work looked for to esteem the peak discharge of the Cascavel River, in function of the changes in the soil use in the watershed, and the precipitations with different intensities and return period, creating hypothetical sceneries of urban expansion starting from the Soil Conservation Service hydrologic model. Was verified that as the impermeable areas rise it promotes considerable increase of the peak discharge, and that this increase is more significant during precipitations with smaller period return, creating Hypothetical scenarios of urban expansion from the hydrologic model Soil Conservation Service. It was found that the increase in impermeable areas at a rate of 50% and 80% led to the increase of 3.2% and 5.1% of the value of CN, and 29.5% of the volume of peak discharges, and that this increase is more significant rainfall during the period of lower return, could cause a increase of the occurrence of floods in the drainage channels of watershed. Therefore aiming the need of the consolidation of a plan director of urban drainage for the studied area.